The comparison between the effect of Glycyrrhizae uralensis (Gan-Cao) and Montelukast on the expression of T-bet and GATA-3 genes in children with allergic asthma - Ping, Zang; Jun, Xue; Yan, Wang; Jun, Zhang (Cellular and Molecular Biology, 2022)
Pediatric allergic asthma is a chronic disease that affects the lungs and airways. If a child is exposed to certain stimulants such as pollen inhalation, colds, or respiratory infections, the lungs become inflamed and if left untreated can lead to dangerous asthma attacks. One of the most important treatments for this disease is the use of leukotriene modulators, such as montelukast. But recently, due to easier access, cheaper prices and fewer side effects, attention has shifted to non-chemical treatments. Gan-Cao (Glycyrrhizae uralensis), as traditional Chinese medicine, has been proved to have a good therapeutic effect on experimental allergic asthma. But its anti-asthma mechanism is currently unclear. Therefore, the study aimed the comparison between the effect of Gan-Cao and montelukast on the expression of T-bet and GATA-3 genes in children with allergic asthma. For this purpose, fifty children with allergic asthma were divided into two groups. The first group was treated with montelukast for one month. The second group was treated with Gan-Cao root extract. Then the peripheral blood mononuclear cells were isolated, their RNA was extracted, and the relative expression of T-bet and GATA3 transcription factors was evaluated by Real-time PCR. The relationship between them and risk factors for asthma was assessed by relevant statistical tests. The result showed the expression of the GATA3 gene (P = 0.102), T-bet gene (P = 0.888), and the expression ratio of T-bet/GATA-3 genes (P = 0.061) was not significantly different between the two groups. It showed that Gan-Cao can affect the expression of these genes just as much as montelukast. Therefore, this Chinese herb can be used as an alternative or supplement medicine to treat allergic asthma in children.